25 Years Pioneering High Altitude and Glacial Archaeology from the Mountains of Argentina - Ceruti, Maria Constanza (2022)
Glacial archaeology is an emerging field of scientific research, rapidly expanding in Scandinavia, the Alps and North America. And yet its origins are to be found in the Andes of Argentina. Constanza Ceruti is the first woman high altitude archaeologist in history. Her pioneering contributions to this field of research involve having ascended and explored, sometimes solo and unsupported, more than one hundred peaks above 5000 meters in remote corners of the Andes. In 1999, Ceruti codirected the scientific excavations on mount Llullaillaco (6739 m), the highest archaeological site in the world, and co-discovered three extraordinarily preserved frozen mummies, together with an outstanding collection of artifacts from the Inca civilization (currently housed at the Museum of Mountain Archaeology in Salta, Argentina). In recent years, Ceruti has climbed hundreds of mountains in different parts of our planet, to study (from an anthropological perspective) their role in pilgrimage, folklore, popular devotion, mythology, identity and tourism. Her academic production includes more than one hundred scientific papers and twenty-five books on sacred mountains of the Americas, Europe, Asia, Australia and Polynesia. A northern hemisphere predominance in anthropology at large, and particularly in high mountain and glacial archaeology (associated also with mobbing and male chauvinsm in mountaineering), have led to a lack of proper recognition, not only for her own pioneering career, but for the rightful place of the Andes at the forefront of academic research on the sacred role of mountains in ancient cultures.